(untitled) (Research, Society and Development, 2023)
Introduction: Delirium is a severe neuropsychiatric syndrome. It is characterized by fluctuating alterations in the level of consciousness, with an acute onset of symptoms. Objective: to identify the prevalence of delirium in (ICU) adults and make the data available to the institution, with the aim of providing information to add to the care and clinical management of these patients. Method: This is a descriptive observational study, with a quantitative approach, carried out in an adult ICU, in a hospital in the interior of Minas Gerais. Data collection was carried out between June and September 2019, through the application of the Confusion Assessment Method in an Intensive Care Unit (CAM-ICU) scale. Results: The sample consisted of 97 patients who met the inclusion criteria of the study, of which 47.42% had a positive diagnosis for delirium in at least one evaluation using the CAM - ICU scale. There was no significant difference in prevalence regarding gender. There was a greater predominance of cases in individuals aged between 60 and 79 years, with the mean age of the study population being 66.3 years. The causes of hospitalization of the selected patients were predominantly cardiovascular, neurological and traumatic problems. About 86.95% of patients with a positive assessment for delirium used mechanical ventilation (MV) and sedation at some point during hospitalization. Conclusion: The prevalence of delirium in the studied ICU is high, reinforcing the need to create protocols in order to identify it early and treat it appropriately.